ILMU SEBAGAI KEKUASAAN PERAN DAN IMPLIKASINYA - Ni Ketut Tri Srilaksmi; Gede Arya Prabawa; Kadek Suciani (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2019)
Human reality, as God's creation, ultimately requires knowledge in understanding the process of human interaction with the nature of humanity. The method of finding experience can be Informed by finding out and doing learning that produces knowledge continuously. Humans need not only expertise but also knowledge to achieve the goals they want to make.